Peran Sultan Mahmud Al-Rasyid Perkasa Alamsyah pada Kesultanan Deli: Tahun 1858-1873 - Nasution, Abdul Gani Jamora; Lubis, Luthfi Adam; Hutapea, Paisal Rahman; Arbaita, Arbaita (YASIN, 2023)
The purpose of this study was to determine the role of the government at the time of Sultan Mahmud Perkasa Al Rasyid Perkasa Alamsyah in the Deli Sultanate. The method used in this study is a qualitative method with data collection techniques of observation, interviews and documentation. The results of the research obtained are, First, the history of the Sultanate of Deli is that the Kingdom of Deli was founded in the first half of the 17th century AD which was founded by Sri Paduka Gocah Pahlawan or with his nickname Mahmud Al-Rasyid Perkasa Alamsyah. On his way, the founding of the empire. In the early 1600s the term Haru or Aru was also replaced by the name Deli. The Haru region then gained its independence from Aceh in 1669, under the name of the Sultanate of Deli. When it became the Sultanate of Deli, all historians agree that the founder of this empire was Seri Paduka Gocah Pahlawan. Until there was a conflict in the change of power in 1720 causing the breakup of Deli and the establishment of the Sultanate of Serdang in 1723. In the context of the government of the Unitary State of the Republic of Indonesia, these two sultanates, today cover the city of Medan. The second is about the biography of the Raja Raja of the Deli Sultanate and the third is his contribution to the Deli Sultanate.